Gastric adenosquamous carcinoma producing granulocyte-colony stimulating factor: a case of a rare malignancy - Kazuki Moro; Masayuki Nagahashi; Tetsuya Naito; Yu Nagai; Tomohiro Katada; Masahiro Minagawa; Jun Hasegawa; Tatsuo Tani; Naohiro Shimakage; Hiroyuki Usuda; Emmanuel Gabriel; Tsutomu Kawaguchi; et al. (Surgical Case Reports, 2017)
Abstract Background A gastric adenosquamous carcinoma (ASC) that produces granulocyte-colony stimulating factor (G-CSF) is an uncommon malignancy with a poor prognosis. Due to the rarity of this lesion, a standard treatment for the disease has not been established. Case presentation We describe a case of a 66-year-old male with a G-CSF-producing gastric ASC who presented with severe anemia and leukocytosis. A radical resection was performed, followed by a course of adjuvant chemotherapy. Histopathologic examination revealed that the tumor consisted of areas of both squamous cell carcinoma and adenocarcinoma. Immunohistochemical staining with an anti-G-CSF antibody was also positive. He was started on adjuvant capecitabine and oxaliplatin (CapeOX) 6 weeks after surgery. The patient stopped treatment after 3 months due to his own preference. Eight months following surgery, the patient was found to have diffuse lymph node, liver, and peritoneal metastases. Conclusions G-CSF-producing gastric ASC is a rare and aggressive tumor. Because patients are usually diagnosed at an advanced stage, multidisciplinary evaluation and innovative treatments are needed. The rarity of this disease, with its aggressive features, poses a significant challenge in its treatment. In this brief case report, we summarize the management and outcomes of G-CSF-producing gastric ASC.